Econometric Analysis of the Efficiency of Production of Horticultural Products - Juraev Farhod Mamadiyorovich (Genius Journals, 2022)
The article reveals the main production factors that affect the increase in the production of horticultural products. In the dissertation work, using a logarithmic-linear model based on the Cobb-Douglas production function, within the framework of the goals and objectives set for the study, as well as their scientific and methodological solutions are substantiated. A forecast was developed for the gross agricultural product of the Tashkent region and innovations introduced into agriculture for 2022-2027.
Keywords: Agriculture; gross product; horticulture; innovation technologies